Retrofitting seismically damaged non-rectangular reinforced concrete walls using fiber-reinforced polymers - Suhartono, Kevin Emanuel (2014)
Reinforced concrete (RC) structural walls are commonly used in the buildings to resist lateral loads, such as winds and earthquakes. However, according to the earlier design code, insufficient seismic detailing was generally adopted in the design of walls in many existing old buildings. Moreover, similar design of RC shear walls with limited transverse reinforcement is also applied in the regions with low to moderate seismicity like Singapore. As a result, these RC walls are vulnerable to damage and collapse in the event of earthquake. In response to the seismically damaged structural walls, various repair and strengthening methods have been introduced to prevent collapse and recover their original structural behavior. One method which has been very popular in the last decade is strengthening damaged RC walls using fiber-reinforced polymer (FRP) composites. In fact, extensive studies have been carried out previously to evaluate the effectiveness of FRP strengthening method on the seismically damaged RC walls. However, most of those researches focused on the test of rectangular RC walls and very limited experimental studies have been conducted on the non-rectangular RC walls. Therefore, the current research was carried out to evaluate the effectiveness of retrofitting damaged non-rectangular RC walls with inferior seismic detailing using FRP sheets and strips. In this study, 2 L- and 2 T-shaped pre-tested specimens under axial and quasi-static cyclic lateral load were selected as the control specimens and their structural behaviors were analyzed. These damaged control specimens were then repaired and strengthened using FRP based on the proposed scheme. Subsequently, the repaired specimens were retested under similar loading condition. The performance of the repaired specimens was then evaluated and compared to that of the original specimens. The results show that the proposed repair and FRP strengthening scheme was able to recover the lateral resisting capacity, in-plane stiffness, and ductility of the damaged non-rectangular RC walls. In addition, an analytical study was conducted by developing and analyzing fiber models to estimate the structural behavior of L- and T-shaped RC walls with FRP jacket. From the analytical study, estimated moment-curvature diagrams of the repaired L- and T- shaped walls tested in the experiment were established, which is useful for future design purpose.